Effects of annealing and quenching temperature on microstructure evolution and mechanical properties in Fe-0.17C-2.10Mn-0.51Si steel - Panpan Yuan; Depeng Shen; Wei Sun; Bingtao Tang (Materials & Design)
The optimum mechanical properties of Fe-0.17C-2.10Mn-0.51Si steel are achieved by adjusting annealing and quenching temperatures. Annealing at 790 °C for 300 s, followed by quenching at 310 °C for 15 s and partitioning at 460 °C for 50 s, results in a tensile strength of 831.8 MPa and an elongation of 27.6 %. This is attributed to a higher volume fraction (13.1 %) and mechanical stability of retained austenite (RA), along with smaller grain size (3.99 µm) and a high proportion of high-angle grain boundaries (83.3 %), enhancing the transformation-induced plasticity (TRIP) effect. With increasing annealing and quenching temperatures, grain size increases. However, annealing temperature raises dislocation density, while quenching temperature reduces it. The fraction of RA initially increases and then decreases with higher annealing and quenching temperatures. XRD analysis shows carbide precipitation at 730 °C shifts peaks to lower angles, while dissolution at 850 °C and 910 °C leads to lattice expansion. Minimal peak shifts at 790 °C correlate with optimal properties. Micro-texture analysis reveals γ-fiber {111}//ND texture in BCC and Rotated-Goss texture in austenite, contributing to the balanced strength and ductility. This study offers insights into optimizing Q&P treatment for excellent mechanical performance.